2006
DOI: 10.1074/jbc.m512137200
|View full text |Cite
|
Sign up to set email alerts
|

Importance of K+-dependent Na+/Ca2+-exchanger 2, NCKX2, in Motor Learning and Memory

Abstract: Plasma membrane Na؉ /Ca 2؉ -exchangers play a predominant role in Ca 2؉ extrusion in brain. Neurons express several different Na ؉ /Ca 2؉ -exchangers belonging to both the K ؉ -independent NCX family and the K ؉ -dependent NCKX family. The unique contributions of each of these proteins to neuronal Ca 2؉ homeostasis and/or physiology remain largely unexplored. To address this question, we generated mice in which the gene encoding the abundant neuronal K ؉ -dependent Na ؉ /Ca 2؉ -exchanger protein, NCKX2, was kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(77 citation statements)
references
References 62 publications
2
73
1
1
Order By: Relevance
“…Inactivation of NCKX2 may be a useful regulatory mechanism that operates under physiological conditions. Mounting evidence points to NCKX2 being an important Ca 2ϩ clearance mechanism in neuronal synaptic terminals (13)(14)(15), which are specialized compartments that experience frequent and dynamic Ca 2ϩ fluxes and depolarized membrane potential resulting from frequent invasions of action potential spikes. Persistent presynaptic activity leads to persistent elevations in presynaptic terminal Ca 2ϩ concentrations (43,44), associated with an increase in intraterminal Na ϩ levels (up to peaks of 80 mM) (45).…”
Section: Controlling Alkali Cation Concentrations Using Gramicidin-mentioning
confidence: 99%
See 1 more Smart Citation
“…Inactivation of NCKX2 may be a useful regulatory mechanism that operates under physiological conditions. Mounting evidence points to NCKX2 being an important Ca 2ϩ clearance mechanism in neuronal synaptic terminals (13)(14)(15), which are specialized compartments that experience frequent and dynamic Ca 2ϩ fluxes and depolarized membrane potential resulting from frequent invasions of action potential spikes. Persistent presynaptic activity leads to persistent elevations in presynaptic terminal Ca 2ϩ concentrations (43,44), associated with an increase in intraterminal Na ϩ levels (up to peaks of 80 mM) (45).…”
Section: Controlling Alkali Cation Concentrations Using Gramicidin-mentioning
confidence: 99%
“…The Na ϩ /Ca 2ϩ -K ϩ exchanger (NCKX) NCKX1 was first reported in retinal rod outer segments and is the isoform on which most extensive physiological studies have been performed (6 -8). NCKX2 transcripts have been reported in the brain and retina (9 -12), and recent emergent evidence indicates that this isoform is important for regulation of Ca 2ϩ levels in synaptic terminals (13)(14)(15). NCKX3 and NCKX4 transcripts are also found in the brain, but have also been localized to smooth muscle of the aorta, uterus, and intestine (16,17).…”
mentioning
confidence: 99%
“…NCKX2, NCKX3, and NCKX4 are broadly expressed in brain with distinct, often overlapping, regional distributions . The expression of NCKX2, the major neuronally expressed isoform (Tsoi et al, 1998;Dong et al, 2001), is limited to cone photoreceptors (Prinsen et al, 2000) and to neurons, where it plays important physiological roles (Tsoi et al, 1998;Li et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…An NCKX2 paralog was also recently cloned from the retina of striped bass, and isolated cone outer segments were shown to contain K + -dependent Na + /Ca 2+ exchange activity (45). However, NCKX2 knockout mice did not display any obvious deficits in either cone number or function, suggesting that either other Ca 2+ efflux pathways compensated for the absence of NCKX2 or that NCKX function plays a more subtle role in Ca 2+ homeostasis in cone photoreceptors that would require more detailed analyses to elucidate (35).…”
Section: Structure and Functionmentioning
confidence: 99%
“…The results of these studies have demonstrated that NCKX proteins play important functional roles in neuronal Ca 2+ signaling, although the precise impact of these exchangers on neuronal function is only beginning to be elucidated. Recently, knockout mice lacking NCKX2 were shown to display deficits in motor learning and memory that could be attributed to compromised hippocampal synaptic plasticity (35). Future studies on acute brain preparations and cultured neurons from mice lacking specific NCKX isoforms will more clearly define their functional roles in Ca 2+ signaling and the subsequent impact on neuronal function.…”
Section: Neuronal Physiologymentioning
confidence: 99%